PSYCHODINAMICS OF DEPRESSION - Avila, Alejandro (Anales de Psicología / Annals of Psychology)
In this paper, the main models that have been formulated by diverse psychoanalytical authors, with respect to description, comprehension and explanation of the phenomenon and processes of Depression, have been critically revised. The reciprocal contributions between S. Freud and K. Abraham, with the models from S. Rado, G. Gero, M. Klein, J. Sandler, O. Kernberg, Ch. Brenner, E. Bibring and E. Jacobson, among others, are specially analyzed. Later, the new theories developped that appeared in the seventies, due to the dialogue between psychoanalysts and cognitivist are revised. From this, a process model evolved for the dynamics of the experiences and phenomenon of depression in the adult, and also a model for psychogenesis of the depressive constellation in infance and adolescence, were developped. Finally, the actual meaning of structural hypotheses (oral pathology, Super-Ego pathology, low self-esteem, pathology of narcissism) are considered.